Mentoring Student Start-Up During Covid19 Pandemic - Silva, Novira da (Dinamika Pendidikan, 2021)
The purpose of this research was to explore mentoring activities for student start-ups in the early covid19 pandemic. Mentoring activities involved faculty members as mentors and final year students as mentees in Undergraduate Business Program at Universitas Prasetiya Mulya. Mentees must initiate a start-up business as a Business Project Thesis. The method of this study was a case study and data collection through interviews with Faculty Members and Focus Group Discussions with student start-up business representatives. The data obtained were analyzed by using pattern analysis. Findings identified digital platform used for virtual mentoring varied from a virtual meeting, document sharing, and communication through chat group. Mentors had settled their role as facilitators, counsellors, and assessors through mentoring activities. Due to the covid19 pandemic, some challenges emerged in business execution and the paper writing process. Both mentor and mentee had adjusted their effort to resolve the challenges. The mentoring activities had given a positive contribution to day-to-day student start-up business operations. The study also provided recommendation for improving mentoring program, the need for careful design and implementation of pre-mentoring activities (mentor allocation and mentor training) and post-mentoring activities including mentor evaluation.